Some selected aspects of management of irrigators' associations in four provinces a Philippine case [microform] - Batoon, Jacinto R. 1940- (Quezon City Photoduplication Service. University of the Philippines Library, 1979)
Thesis (M.A.)--University of the Philippines, Los Banos.
Microfilmed with 9 other titles.
Appendices: leaves 105-126.
Chiefly tables.
Microfilm of a mimeographed text.
Vita.
Originally published in 1978.
Keywords: Irrigation societies -- Philippines; Agricultural societies -- Philippines